2017
DOI: 10.4314/ecajs.v22i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and management of priapism in a tertiary hospital of North-Western Nigeria

Abstract: Background: Priapism is a persistent penile erection that continues for more than four hours beyond sexual stimulation and orgasm or unrelated to sexual stimulation 1 . The objective is to document the pattern and management of priapism in our hospital. Methods: This is a retrospective study of patients managed for Priapism by Urology Unit of our hospital, from January 2009 to December 2015. Results: Thirty patients were managed for managed for priapism within the study period. The mean age at presentation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Researches that carried out in Sudan in the field of urology discussed the problems of UTIs and their complications, but there was no data about urosepsis, whichis a health problem with global concern. It was found that 30% of sepsis cases are suffered from urosepsis and mainly due to obstruction in various urogenital tract [16] [17] [18] with urosepsis [2]. The current findings showed that urosepsis is more frequently in male than female [18], although females were more affected by UTIs and complications.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Researches that carried out in Sudan in the field of urology discussed the problems of UTIs and their complications, but there was no data about urosepsis, whichis a health problem with global concern. It was found that 30% of sepsis cases are suffered from urosepsis and mainly due to obstruction in various urogenital tract [16] [17] [18] with urosepsis [2]. The current findings showed that urosepsis is more frequently in male than female [18], although females were more affected by UTIs and complications.…”
Section: Discussionmentioning
confidence: 52%
“…It was found that 30% of sepsis cases are suffered from urosepsis and mainly due to obstruction in various urogenital tract [16] [17] [18] with urosepsis [2]. The current findings showed that urosepsis is more frequently in male than female [18], although females were more affected by UTIs and complications. Certain urological obstruction are related to male only and this include; benign prostatic hyperplasia, prostate cancer and urethral stricture [19].…”
Section: Discussionmentioning
confidence: 52%
“…The findings in this report stress the fact that patients with priapism should be evaluated emergently to identify the sub-type of priapism. This is because priapism, as multiple reports have shown, requires prompt evaluation and usually requires emergency management [1,19]. Therefore, those with an acute ischemic event, as identified clinically in this report, should be provided early and prompt clinical intervention [20].…”
Section: Discussionmentioning
confidence: 89%
“…Priapism is a rare pathological condition, characterized by a persistent and painful penile erection that persists beyond four (4) hours and is not related to sexual stimulation [1]. Priapism is considered a serious adverse drug reaction because it requires urgent intervention to preserve the erectile ability of corpora cavernosa [2].…”
Section: Introductionmentioning
confidence: 99%
“…The cavernous vein communicates with the emissary veins through the subtunica venous plexus, and these veins are compressed during erection. 3 Abnormality with adequate arterial and venous return during erection may result in persistent painful erection, especially in ischaemic priapism; 2,4 as well as penile fracture that occurs during sexual intercourse, when the penis slips outside the vagina, and hits the inferior pubic rami bone. 5,6 There is an association between lichen sclerosus et atrophicus and penile cancer.…”
Section: Introductionmentioning
confidence: 99%